PENGARUH KINERJA GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE, DAN REPUTASI AUDITOR TERHADAP MANAJEMEN LABA PADA PERUSAHAAN YANG MENGIKUTI PROGRAM CORPORATE GOVERNANCE PERCEPTION INDEX - Awaludin Akbar, 10.05.52.0002; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2014)
Earnings management is the manager of a deliberate attempt to manipulate the financial statements within the limits permitted by accounting principles with the aim of providing misleading information for the users of the financial statements for the benefit of the manager. This study aimed to examine the effect of good corporate governance performance, firm size, profitability, financial leverage, and the reputation of the auditor on earnings management.This study used secondary data from the 52 sample companies that follow the corporate governance program preception CGPI index 2010-2012. The dependent variable in this research is earnings management, while the independent variable is the performance of good corporate governance, company size, profitability, leverage, and auditor reputation. Analysis using multiple linear regression analysis.Test results found evidence that (a) good corporate governance and significant negative effect on earnings management. (b) the size of the company and no significant negative effect on earnings management. (c) profitability and significant positive effect on earnings management. (d) financial leverage has a positive effect on earnings management. (e) the auditors reputation and a significant positive effect on earnings management.Keywords: corporate governance performance, firm size, profitability, financial leverage, auditor reputation and earnings managementÂ